A Study to Assess the Effectiveness of Planned Teaching Program Regarding Prevention and Management of Side-effects of Chemotherapy in Terms of Knowledge and Attitude among Cancer Patients: A Pre-experimental Study - Sehgal, Monika (Innovational: Journal of Nursing and Healthcare, 2024)
Introduction: Cancer describes the disease that results when cellular changes cause the uncontrolled growth and division of cells. Although chemotherapy is an effective way to treat many types of cancer, chemotherapy treatment also carries a risk of side-effects. Planned teaching program (PTP) is one of the most effective teaching strategies, which can be used for improving the knowledge of cancer patients. Aim: The aim of the study was to assess the effectiveness of PTP in improving the knowledge and attitude of cancer patients in the prevention and management of side-effects. Methodology: Research design used in the study was pre-experimental (one group pre-test and post-test) design. A total of 35 samples were selected using a systematic random sampling technique. PTP was developed. A structured knowledge questionnaire and attitude rating scale were used to collect the demographic characteristics and assess the level of knowledge and attitude followed by PTP and post-test. Results: The findings revealed that pre-test knowledge score was (12.65±4.19) and post-test knowledge score (25.54±3.39). The “t” value (17.40) was found to be significant at 0.05 level of significance. Pre-test attitude score was (68.51±9.79) and post-test attitude score was (79.62±7.87). The “t” value (8.07) was found to be significant at 0.05 level of significance. There was a weak positive correlation 0.43 that existed between the knowledge and attitude scores. Conclusion: The study concluded that the PTP was effective in increasing the knowledge scores and attitude scores regarding the prevention and management of side-effects of chemotherapy. Early diagnosis remains the cornerstone in cancer control with a comprehensive education on the prevention and management of side-effects of chemotherapy